Feasibility study on the Development of Higher Education Repository X in Pagar Alam, South Sumatra - Muslim, Buhori (Jurnal Ilmiah Sistem Informasi, 2023)
Higher education is an institution that has various sections and work units that work together in carrying out the Tri Dharma principles, namely research, learning and service, which are able to accommodate large amounts of data, both in conventional and digital forms. digitally it is called a repository, college x in Pagar Alam, South Sumatra does not yet have a repository, so a feasibility study must be carried out which can later become a forum for suggestions. Before the repository is developed, a feasibility study must be carried out so that the development can be carried out properly. This feasibility study is first carried out through the management life cycle, where this research includes survey method re- search. This research produces data from an infrastructure feasibility study in building a repository for Higher Education x in Pagar Alam, South Sumatra, which is 80%, this percentage is obtained from infrastructure feasibility 40%, HR 10%, Budget 0%, SPMI (SOP/SK) of 10 %, and 20% repository content. The things that need to be fixed are the availability and addition of IT infrastructure, software, additional rules (SOP), and procedures for submitting and uploading data.